Frailty and Kidney Transplantation: A Systematic Review and Meta-analysis. Issue 6 (18th May 2021) - Quint, Evelien E.; Zogaj, Donika; Banning, Louise B.D.; Benjamens, Stan; Annema, Coby; Bakker, Stephan J.L.; Nieuwenhuijs-Moeke, Gertrude J.; Segev, Dorry L.; McAdams-DeMarco, Mara A.; Pol, Robert A.
Abstract : Background: Frailty is a multidimensional condition and is the result of the body's age-associated decline in physical, cognitive, physiological, and immune reserves. The aim of this systematic review is to assess the quality of evidence of the included studies, determine the prevalence of frailty among kidney transplant candidates, and evaluate the relationship between frailty and associated patient characteristics and outcomes after kidney transplantation. Methods: A systematic search was performed for relevant literature on frailty and kidney transplantation. This was followed by a meta-analysis for patient characteristics and outcomes reported by a minimum of 2 studies including mean age, gender, mean body mass index, type of kidney transplantation, dialysis, previous kidney transplantation, comorbidities, hypertension, race, preemptive kidney transplantation, delayed graft function, and length of stay. Results: A total of 18 studies were included in the systematic review and 14 of those studies were suitable for meta-analysis. The overall pooled prevalence of frailty before transplantation was estimated at 17.1% (95% confidence interval [CI], 15.4-18.7). Frailty was significantly associated with higher age (mean difference, 3.6; 95% CI, 1.4-5.9), lower rate of preemptive transplantation (relative risk, 0.60; 95% CI, 0.4-0.9), longer duration of delayed graft function (relative risk, 1.80; 95% CI, 1.1-3.0), and length of stay longer than 2 wk (odds ratio, 1.64; 95% CI, 1.2-2.3). Conclusions: One in 6 kidney transplant recipients is frail before transplantation. The presence of frailty is associated with lower rates of preemptive transplantation, older recipient age, higher rates of delayed graft function, and longer length of stay. Future research is required to explore the association of frailty with other adverse outcomes after kidney transplantation and the effects of intervention programs to improve the different frailty domains.